Presentation of the monographic issue. Kaleidoscopic views that problematise intercultural education from a decolonial perspective - Ester Caparrós Martín; Giuseppe Burgio (University of Bologna, 2023)
With this brief text we would like to present the monograph that concerns us, entitled Thinking a postcolonial pedagogy to decolonise education. In this sense, several questions seem to us important today in relation to intercultural education: on the one hand, we problematise the sense in which this notion is still approached both in educational discourses and practices; on the other hand, we ask ourselves the following question: can we think today about intercultural pedagogy and education without first assuming the historical and political caesura constituted by colonialism? We will review and present in general terms the themes that the various authors participating in this monograph have sent us and which offer a kaleidoscopic view of the subject that concerns us: decolonising intercultural education.